Memitigasi Peran Orang Tua Di Keluarga Kristen Dalam Menanggulangi Dampak Disinformasi Dari Bingkai Teologi Pentakosta - Kosma Manurung (Sabda: Jurnal Teologi Kristen, 2021)
The period in which believers live today is a time marked by the ease with which information is obtained. Unfortunately not all information is good, correct, and useful because there is a lot of information circulating out there that is deliberately created to spread hatred, lies, moral depravity, and various other acts that are contrary to Christian faith. The purpose of this article's research is to illustrate the important role that parents in Christian families can play in overcoming the disinformation impact of the Pentecostal theological framework. In this study, researchers used a descriptive analysis method and literature review. The results of this study offer four practical steps that parents in Christian families can take in stemming disinformation in their families, namely by taking protective measures in the form of regulating and restricting children's access to the internet, providing assistance, opening discussion spaces, and being examples that can be followed. by the child.